2017
DOI: 10.22365/jpsych.2017.283.259
|View full text |Cite
|
Sign up to set email alerts
|

Employment insecurity, mental health and suicide

Abstract: With the economic crisis an increase in suicidality has been reported across Europe but especially in Greece. Τhese reports hit the mass media headlines and were also included in the debate among political parties. The literature suggests that during periods of deep economic crisis, there is an increase specifically in suicides but causality remains unclear. The prevailing picture both in the scientific literature and in the mass media is that the economic crisis acts as a more or less generic risk factor on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Unemployment can lead to mental fatigue, a depressive state, or psychiatric disorders, all of which can lead to suicide [ 44 , 45 , 46 ]. Our present analyses uncovered two major points regarding the features of suicide linked to unemployment in many of the post-Soviet countries: (1) the suicide rates of both males and females were significantly associated with the unemployment rate in nearly half of the 15 countries, and (2) for nearly 70% of the males in the entire set of 15 countries, there was a significant association between the suicide rate and the unemployment rate.…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment can lead to mental fatigue, a depressive state, or psychiatric disorders, all of which can lead to suicide [ 44 , 45 , 46 ]. Our present analyses uncovered two major points regarding the features of suicide linked to unemployment in many of the post-Soviet countries: (1) the suicide rates of both males and females were significantly associated with the unemployment rate in nearly half of the 15 countries, and (2) for nearly 70% of the males in the entire set of 15 countries, there was a significant association between the suicide rate and the unemployment rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search yielded several studies conducted in developed countries that obtained similar results [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 34 ]. Another study reported that suicides increase especially during periods of severe economic crisis [ 35 ]. Widespread economic downturn and unemployment cause personal hardships; if those hardships continue, they can lead to mental exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…While almost one in every four people will suffer from a mental illness at some time in their lives and the overall burden of disease is above 15% of total burden (Benyamina, Blecha, & Reynaud, 2012;Bertolote & Fleischmann, 2002;Collins et al, 2011;Fountoulakis, 2016Fountoulakis, , 2017Fountoulakis & Gonda, 2017Fountoulakis et al, 2015;Gore et al, 2011;Harhay & King, 2012;O'Connor & Sheehy, 2000;Ormel et al, 2008), there is a widespread stigma related to mental illness at a global scale.…”
Section: Introductionmentioning
confidence: 99%